Comparative study on dielectric performance between vegetable-based and mineral-based oil under accelerated thermal ageing and loaded distribution transformer - Mohd.Taib, Mohd. Fikri Hilmi (2018)
Mineral insulation oils are generally used for electric power apparatus as insulators and cooling medium. Since mineral oils are not biodegradable, have low flash points and are difficult to decompose, there is a need for the development of vegetable-based insulation oils for such applications. This study is conducted to investigate the physical, electrical and chemical ageing performances of vegetablebased oils for transformer fluid application against mineral oil. First, the accelerated thermal ageing was carried out on three different types of vegetable-based oils and existing mineral oil at 130˚C under sealed conditions for several period of times (0, 50, 200, 500 and 1,000 hours). The vegetable-based oils were palm-based oils (HiLECT oil and Palm Fatty Acid Ester (PFAE)) and one type of soybean-based oil (Envirotemp® FR3). The effects in terms of visual observation, viscosity, dielectric strength and moisture content were discussed in detail. Sequentially, two units of three phase hermetically sealed distribution transformers (100 kVA, 11 kV/415 V) filled with mineral oil and HiLECT oil were constantly loaded at a high load (72%) at several period of times (0, 500 and 1,000 hours) under laboratory condition. The ageing performance comparisons were done in terms of visual observation, viscosity, dielectric strength, dissipation factor, moisture content, acidity and dissolved gas analysis. The study shows that HiLECT oil is suitable to be used as an alternative transformer insulation oil due to its good dielectric ageing properties compared to mineral oil, PFAE and FR3. In addition, its viscosity is seen as adequate for the transformer’s cooling medium application even though its viscosity is 10 times higher than PFAE and 3.4 times higher than mineral oil. On the other hand, paper immersed in HiLECT oil degrades around 2 times slower than the paper immersed in mineral oil. In conclusion, the comparison revealed that HiLECT oil has better characteristics than mineral oil in prolonging transformer’s lifetime.